Alamat ng butanding The legend of the whale shark - Matias, Segundo D.; Ranola, Jonathan; Bravo, Becky; Garcia, Edith (Quezon City Lampara Publishing House, Inc., 2011)
"A long time ago, there was a man whom everyone was afraid of because of his size. Nobody knew why he grew so large. Because of this, there were not any clothes that fit him, so he covered his body instead with leaves and bits of tree bark patched together. But because of some calamities that came to the village, Tanding proved how important he was to the people. Find out in this story how a gentle giant became a whale shark."
Stories with moral values
Text in Filipino and English.
Keywords: Whale shark -- Fiction